Analisis Terjemahan Q.S An-Naba’: 1-7 dalam Tafsir Bacaan Mulia Karya H.B. Jassin - Muhammad Akhyar Rifa'i; Muhammad Fathur Rahman; Ardhi Ilhamul Birry; Hasani Ahmad Said (Jurnal test, 2024)
Literature is believed to have a special appeal for the majority of people from all nations, including Arabs and Indonesians. The Al-Qur'an, which uses noble literature, was translated using literary language by H.B Jassin. His thoughts attract the attention of writers because they transmit literature to literature. This study aims to describe the verses of An-Naba from 1-7 in the perspective of the translation of the Noble Readings by H.B. Jassin. This study uses a descriptive analysis method without using statistical figures, the source of the research data is from Tafsir Noble Readings and Surah An-Naba. The results of this study are as follows: 1) Personality of H.B. Jassin who became his motivation to write the translation; 2) Ijmali and Tahlili methods are used to analyze and collect data; and 3) The language style of this Noble Reading translation is in the form of poetry, different from the translation of the Ministry of Religion. This translation of the Noble Readings does not change the meaning, meaning and content of the Qur'an at all, it's just that the difference is in the language style and sentence structure used by H.B. Jassin. H.B.'s goal Jassin wrote his translation solely to make the verses of the Qur'an very beautiful.